The Effect of Pricing on Consumer Purchase Decisions - Wirawan, Andri (Adpebi Science Series, 2022)
For the last few years, the company's sales are known to continue to decline. This decline is also assessed because consumer purchasing decisions at the company continue to decline so that it does not confuse the company the longer it looks like the consumers who make purchases are increasingly quiet. Pricing for the products and services offered by the company is perceived to be higher than that of other companies. This makes consumers feel a bit at a loss because if consumers switch to other companies, consumers can also save the costs they have to spend to obtain these products such as the difference in costs incurred to buy products at the company compared to if they make purchases at other companies.The purpose of this study was to determine the effect of pricing on purchasing decisions at PT. Dodorindo Jaya Abadi Tanjung Morawa.The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The research population that will be used in the study are all consumers who make purchases at the company during the 2021 period as many as 212 consumers. Because the population used is 212 consumers, the population will be reduced by using the Slovin sampling technique with a 95% confidence level and an error rate of 5%, where 139 samples are obtained. The analytical technique used is multiple linear analysis and statistical tests, namely t-test (partial) and F-test (simultaneous) using SPSS (statistical package for the social sciences) software.The test results show that partially the pricing variable has a positive and significant effect on purchasing decisions where the influence given is 21.1%.The conclusion of this study is that partially, the pricing variable has a positive and significant effect on purchasing decisions at PT. Dodorindo Jaya Abadi Tanjung Morawa.